2019
DOI: 10.21203/rs.2.17915/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Panfungal PCR assays using fresh frozen paraffin embedded tissue specimens for fungal species identification and the detection of azole-resistance mutations in the A. fumigatus cyp51A gene at a South Korean hospital

Abstract: Background: With rising concerns about changing fungal epidemiology and azole resistance in Aspergillus species, identifying fungal species and susceptibility patterns of mucorales and aspergillosis are crucial in the management of these diseases. The objectives of this study were to evaluate performance of panfungal PCR assays on formalin-fixed paraffin embedded (FFPE) samples for fungal species identification, and the detection of azole-resistance mutations in the Aspergillus fumigatus ( A.fumigatus ) cyp51A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although the site of the infection may affect the results, to set up a method independent of histopathological tests, in this study, a part of the sample was randomly taken from a PEB. While Jung et al reported a 41.3% positive rate for panfungal PCR due to long amplicon length and perhaps an ineffective DNA extraction kit 37 . This work found a concordance rate of 76% between semi‐nested PCR of the ITS region and histopathology tests, while others reported higher 21 or lower 38,39 concordance rates between these two methods.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although the site of the infection may affect the results, to set up a method independent of histopathological tests, in this study, a part of the sample was randomly taken from a PEB. While Jung et al reported a 41.3% positive rate for panfungal PCR due to long amplicon length and perhaps an ineffective DNA extraction kit 37 . This work found a concordance rate of 76% between semi‐nested PCR of the ITS region and histopathology tests, while others reported higher 21 or lower 38,39 concordance rates between these two methods.…”
Section: Discussionmentioning
confidence: 65%
“…While Jung et al reported a 41.3% positive rate for panfungal PCR due to long amplicon length and perhaps an ineffective DNA extraction kit. 37 This work found a concordance rate of 76% between semi‐nested PCR of the ITS region and histopathology tests, while others reported higher 21 or lower 38 , 39 concordance rates between these two methods.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation